Relationship Between ACTN3 R577X Polymorphism and Physical Abilities in Polish Athletes. Issue 8 (August 2015) - Orysiak, Joanna; Busko, Krzysztof; Mazur-RóŻycka, Joanna; Michalski, Radoslaw; Gajewski, Jan; Malczewska-Lenczowska, Jadwiga; Sitkowski, Dariusz
Abstract : Abstract: Orysiak, J, Busko, K, Mazur-Różycka, J, Michalski, R, Gajewski, J, Malczewska-Lenczowska, J, and Sitkowski, D. Relationship between ACTN3 R577X polymorphism and physical abilities in polish athletes. J Strength Cond Res 29(8): 2333–2339, 2015—The purpose of this study was to examine the association between α-actinin 3 ( ACTN3 ) R577X polymorphism and physical abilities of male athletes performing various sports (volleyball, ice hockey, canoeing, swimming). One hundred eighty-five subjects were recruited for the study. The following measurements were taken: height of jump and power output in countermovement jump and spike jump (SPJ) and muscle strength of 10 muscle groups. The R577X polymorphism of ACTN3 was typed using polymerase chain reaction restriction fragment length polymorphism. The results showed that RR genotype carriers develop greater power output in SPJ than RX and XX individuals (44.6 ± 11.1, 42.6 ± 11.0, and 38.4 ± 7.9 W·kg −1 for RR, RX, and XX genotypes, respectively) and height of jump in SPJ (0.537 ± 0.075, 0.523 ± 0.072, and 0.498 ± 0.053 m for RR, RX, and XX genotypes, respectively). Muscle strength did not differ between genotype groups. This suggests that the ACTN3 gene has a greater impact on determining dynamic movements than influencing static muscle strength.